Research Production at King Khalid University: Perceptions, Challenges, and Suggestions for Improvement - Fadi Al-Khasawneh; Mohammad Ahmad Al-Khasawneh; Mohammad Abedrabbu Al-Khawaldeh (Universitas Pendidikan Ganesha, 2021)
Scientific research is very important since it contributes to the development of nations worldwide. However, there is a scarcity of empirical research conducted to investigate the challenges of research production among faculty members at universities. The present study seeks to explore the perceptions, challenges, and suggestions to improve research production at King Khalid University, Saudi Arabia. A questionnaire) was used to collect the data of the present study. The sample of this study included 55 faculty members from the Faculty of Languages and Translation at King Khalid University. The findings revealed that the long waiting period for manuscript publication, lack of allocated time for research, and lack of research training programs were the most prominent challenges in research production. The participants have also stated some suggestions to improve research production such as conducting research training programs, providing research incentives, and providing adequate research facilities.